A New Determinant Expression of the Zeta Function for a Hypergraph - Sato, Iwao (The Electronic Journal of Combinatorics, 2009)
Recently, Storm defined the Ihara-Selberg zeta function of a hypergraph, and gave two determinant expressions of it by the Perron-Frobenius operator of a digraph and a deformation of the usual Laplacian of a graph. We present a new determinant expression for the Ihara-Selberg zeta function of a hypergraph, and give a linear algebraic proof of Storm’s Theorem. Furthermore, we generalize these results to the Bartholdi zeta function of a hypergraph.